Pengaruh Penerapan Model Kooperatif Student Facilitator And Explaining (SFE) Dengan Media LKPD Terhadap Kemampuan Representasi Matematis Siswa - Fuji Rastuti, Hesti; Baidowi, Baidowi; Tyaningsih, Ratna Yulis (FKIP Universitas Mataram, 2025)
This study aims to determine whether the mathematical representation ability of students taught using the Student Facilitator and Explaining (SFE) learning model with LKPD media is better than that of students taught using the direct instruction model at SMPN 7 Mataram. The research method used is a quasi-experimental design with a posttest-only control group design. The population consisted of eighth-grade students at SMPN 7 Mataram, with the sample comprising 42 students from class VIII-J as the experimental group and 42 students from class VIII-I as the control group, selected through purposive sampling. The experimental class was taught using the SFE learning model, while the control class received direct instruction. Data were collected through a mathematical representation ability test. The results of the t-test showed that ​, namely 7.04002 > 1.664, indicating that was accepted. This means that the average mathematical representation ability of the experimental class was higher than that of the control class. Based on these results, it can be concluded that students who received instruction using the SFE model had better mathematical representation abilities compared to those who received direct instruction.